Atherosclerotic Cardiovascular Events in Patients Infected With Human Immunodeficiency Virus and Hepatitis C Virus. (20th July 2020) - Tan, Boun Kim; Chalouni, Mathieu; Ceron, Dominique Salmon; Cinaud, Alexandre; Esterle, Laure; Loko, Marc Arthur; Katlama, Christine; Poizot-Martin, Isabelle; Neau, Didier; Chas, Julie; Morlat, Philippe; Rosenthal, Eric; et al.
Abstract: Background: An increased risk of cardiovascular disease (CVD) was reported in patients coinfected with human immunodeficiency virus (HIV) and hepatitis C virus (HCV), without identifying factors associated with atherosclerotic CVD (ASCVD) events. Methods: HIV-HCV coinfected patients were enrolled in the Agence Nationale de Recherches sur le Sida et les hépatites virales (ANRS) CO13 HEPAVIH nationwide cohort. Primary outcome was total ASCVD events. Secondary outcomes were coronary and/or cerebral ASCVD events, and peripheral artery disease (PAD) ASCVD events. Incidences were estimated using the Aalen-Johansen method. Factors associated with ASCVD were identified using cause-specific Cox proportional hazards models. Results: At baseline, median age of the study population (N = 1213) was 45.4 (interquartile range [IQR] 42.1−49.0) years and 70.3% were men. After a median follow-up of 5.1 (IQR 3.9−7.0) years, the incidence was 6.98 (95% confidence interval [CI], 5.19−9.38) per 1000 person-years for total ASCVD events, 4.01 (2.78−6.00) for coronary and/or cerebral events, and 3.17 (2.05−4.92) for PAD ASCVD events. Aging (hazard ratio [HR] 1.06; 95% CI, 1.01−1.12), prior CVD (HR 8.48; 95% CI, 3.14−22.91), high total cholesterol (HR 1.43; 95% CI, 1.11−1.83), high-density lipoprotein cholesterol (HR 0.22; 95% CI, 0.08−0.63), statin use (HR 3.31; 95% CI, 1.31−8.38), and high alcohol intake (HR 3.18; 95% CI, 1.35−7.52) were independently associated with total ASCVD events, whereas undetectable baseline viral load (HR 0.41, 95% CI, 0.18−0.96) was associated with coronary and/or cerebral events. Conclusions: HIV-HCV coinfected patients experienced a high incidence of ASCVD events. Some traditional cardiovascular risk factors were the main determinants of ASCVD. Controlling cholesterol abnormalities and maintaining undetectable HIV RNA are essential to control cardiovascular risk. Abstract : A high incidence of ASCVD events was observed in 1213 Human Immunodeficiency Virus (HIV)-Hepatitis C Virus coinfected patients. These events were associated with traditional cardiovascular risk factors, whereas high-density lipoprotein-cholesterol levels and controlled HIV RNA were associated with a lower incidence.